Meningkatkan Keterampilan Berbicara Bahasa Inggris Mahasiswa Program Studi Administrasi Rumah Sakit angkatan 17 Dengan Menggunakan Teknik Wawancara terhadap Turis: Improving the English Speaking Skill of the 17th Hospital Administration Students Using Three Steps Interview to Foreigners - Karmilah Karmilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2019)
Referring to the Vision of Politeknik Al Islam Bandung , which is to become a leading higher education institution in the field of health that is appropriate, islamic, national standard and internationally oriented